2016
DOI: 10.1186/s12974-016-0485-y
|View full text |Cite
|
Sign up to set email alerts
|

Complement component C3a plays a critical role in endothelial activation and leukocyte recruitment into the brain

Abstract: BackgroundThe complement system is becoming increasingly recognized as a key participant in many neurodegenerative diseases of the brain. Complement-deficient animals exhibit reduced neuroinflammation.MethodsIn the present study, we administered intracerebroventricularly lipopolysaccharide (LPS) to mimic local infection of the brain and investigated the role of key complement component C3 in brain vasculature endothelial activation and leukocyte recruitment. The degree of neutrophil infiltration was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 54 publications
2
60
0
Order By: Relevance
“…Substantial evidence has indicated that certain chemokines and complement components contribute to the recruitment and activation of lymphocytes . Our data indicate that the increased level of CCL5 is induced by PGLYRP2 (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Substantial evidence has indicated that certain chemokines and complement components contribute to the recruitment and activation of lymphocytes . Our data indicate that the increased level of CCL5 is induced by PGLYRP2 (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Role of the complement system is also increasingly recognized as contributor to the brain endothelial activation (Wu et al, 2016). Moreover, the critical contribution of microglia to the repair of damaged BBB, which involves mechanisms elicited by purinergic receptor signaling, has been demonstrated recently (Lou et al, 2016).…”
Section: Microvascular/blood Brain Barrier Transcriptome Signaturementioning
confidence: 99%
“…Thus, molecular mechanisms that target endothelial activation could be potential therapeutic targets for CNS inflammation . Blockade of leukocyte adhesion to the endothelium by antibodies or other antagonists has been found to reduce CNS inflammatory conditions . In clinical trials of antileukocyte recruitment therapy, interference with leukocyte‐endothelial interactions by targeting adhesion molecules can relieve chronic inflammation in patients with multiple sclerosis …”
Section: Introductionmentioning
confidence: 99%